The effect of motherhood and work on women's time pressure: A cohort analysis using the Australian Longitudinal Study on Women's Health - Otterbach, Steffen; Tavener, Meredith; Forder, Peta; Powers, Jennifer; Loxton, Deborah; Byles, Julie (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVES ': 'The aim of this study was to analyze the prevalence and determinants of time pressure among younger Australian women born between 1973 and 1978 over a 17-year period. ' ' METHODS ': 'Using six surveys (N=14 247 at baseline in 1996) from the Australian Longitudinal Study on Women`s Health (ALSWH), we estimated fixed-effects ordered logistic regression models. ' ' RESULTS ': 'More than two thirds of women felt rushed, pressured, too busy every day or a few times a week, and time pressure substantially increased over the observed 17-year period. Baseline estimates show that time pressure is significantly (P<0.001) associated with being employed and being a mother with coefficients ranging from 0.255 [95% confidence interval (95% CI) 0.188–0.322] for being employed to 0.273 (95% CI 0.168–0.377) for having children. The multivariate analysis further indicates that time pressure is significantly related to a number of personal, family, and work characteristics such as number and age of children, economic insecurity such as having financial difficulties, concern about employment stability, or the length of the working week. ' ' CONCLUSIONS ': 'Understanding the sources of time pressure and identification of certain groups which are particularly vulnerable to it is important if policy-makers aim to design and successfully implement health policies, and family-friendly parental leave and child-care policies.
Keywords: Australia; Australian Longitudinal Study on Women's Health; cohort analysis; motherhood; time pressure; time stress; work; working women